Development of an appropriate PCR system for the reclassification of Streptococcus suis - Ishida, Sakura; Tien, Le Hong Thuy; Osawa, Ro; Tohya, Mari; Nomoto, Ryohei; Kawamura, Yoshiaki; Takahashi, Tatsuhumi; Kikuchi, Naoya; Kikuchi, Ken; Sekizaki, Tsutomu (Journal of microbiological methods, 2014)
Thirty-five serotypes of Streptococcus suis (serotypes 1–34 and serotype 1/2) have so far been described on the basis of their polysaccharide capsular antigens. However, in the last decade, some serotype reference strains have been reexamined for their taxonomic status, and the reference strains of serotypes 20, 22, 26, 32, 33, and 34 may be different from taxon S. suis. In the present study, we developed a novel PCR method targeting the recombination/repair protein (recN) gene of S. suis, designated recN PCR, which corresponds to the current reclassification of this bacterium. We compared its specificity with other PCR methods for S. suis, and the results obtained confirmed its specificity. In addition, the detection limits of recN PCR were similar among all the reference strains of authentic S. suis, indicating that the recN PCR gave reliable results against bacterial strains and isolates used in this study. Therefore, recN PCR described in the present study will be a useful tool for the identification of authentic S. suis, and can also be used in epidemiological studies on this bacterium. •We developed a PCR system for the identification of authentic Streptococcus suis.•Our PCR assay has high specificity.•The sensitivity of our PCR assay is higher than a conventional PCR assay.•Our PCR assay is applicable for field samples.